(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article addresses the enhancement of marketing management for Uzbekistan’s textile enterprises, focusing on the integration of digital strategies with traditional marketing to boost competitiveness. It analyzes current practices, identifies gaps, and proposes strategic recommendations, including digital adoption, e-commerce, and sustainability. The findings suggest that embracing these strategies is crucial for Uzbekistan’s textile industry to thrive in the global marketplace.